Purification, kinetics and spectral characterisation of a new versatile peroxidase from a Bjerkandera Sp. isolate - Moreira, Patrícia R. (2010)
From the extracellular fluid of a novel strain of Bjerkandera sp., it was isolated, purified and identified the main enzyme responsible for Remazol Brilliant Blue R dye decolourisation. Such an enzyme is able to oxidise manganese, as well as veratryl alcohol and 2,6-dimethoxyphenol in manganese-independent reactions; hence, it can be included in the new group of versatile peroxidases. The molecular mass of said enzyme is ca. 45 kDa, and the N-terminal amino acid sequence obtained by Edman degradation is VAXPDGVNTA. The enzyme substrate range for oxidation of several phenolic and non-phenolic aromatic compounds was determined and the corresponding Michaelis-Menten kinetic constants calculated. Furthermore, spectrophotometric assays showing the Soret band and allowing observation of band shifts of the enzyme led to the conclusion that Bjerkandera strains may also synthesise at least two different versatile peroxidases, as happens with Pleurotus eryngii.